Gambaran Self Regulation pada Mahasiswi S1 yang Berperan Ganda sebagai Ibu Bekerja - Sinaga, Lamria (JURNAL DIAKONIA, 2021)
This research aims to get a picture of self-regulation in undergraduate students who play a dual role as working mothers. It is also to get a picture of the subject's ability to implement an effective and efficient self-regulation strategy so that the subject avoids the negative impact that will be received. The number of subjects in this study were three people. This study included research descriptive research. According to the method of data collection, this study used cross-sectional research, where data is taken only once in a period of time. Data collection is done by interview and observation methods. The results of this study indicate that the research subjects try to make themselves feel comfortable by following the right path so that subjects can feel happy while undergoing all roles. The relative like husband and other family members make the subjects more enthusiastic in carrying out his dual role.